Polymer-Enhanced Capillary Transient Isotachophoresis with Boronic Acid-Functionalized Squarylium Dyes for the Fluorescent Determination of Digoxin and Digoxigenin. (2nd November 2017) - Sebaiy, Mahmoud M.; Colyer, Christa L.
ABSTRACT: Here is reported a new application of polymer-enhanced capillary transient isotachophoresis for the separation and quantification of the drug digoxin and its primary metabolite digoxigenin coupled with laser-induced fluorescence (LIF) detection facilitated by labeling with two boronic acid-functionalized squarylium dyes of different alkyl side chain lengths, SQ-BA1 and SQ-BA2. The conditions for drug–dye complex formation were optimized, as determined by absorbance and fluorescence spectra, according to solution pH and buffer composition. As digoxin has a digitoxose sugar moiety in its structure, it was shown to exhibit better enhancement in the fluorescence intensity of both dyes than digoxigenin, which lacks this moiety, presumably through the formation of a cyclic boronate ester complex. A comparison of analyte labeling in pre-column and on-column modes was conducted in subsequent capillary electrophoresis-LIF studies, with the latter labeling mode yielding superior sensitivity. However, to achieve the complete resolution of labeled digoxin and digoxigenin analytes, it was necessary to use the modified isotachophoresis method, with added borate ions that may differentially interact with the drug and its metabolite, hence affecting their mobilities. Limits of quantification of the method for the determination of digoxin with SQ-BA1 and SQ-BA2 were 2.61 × 10 −3 and 2.82 × 10 −3  M and limits of detection were 7.83 × 10 −4 and 8.47 × 10 −4  M while sensitivities were as great as 5.06 × 10 9 and 2.89 × 10 9  M −1, respectively, indicating that the method is suitable for practical analysis.